A Novel Control Method to Improve Current Regulation and Harmonics in Navigation Dimming Power Supply - Zhang Sun; Fan Wu; Weidong Jin; Jun Wang; Yunpu Wu; Xunbing Wu; Zhongjun Wei (IEEE Access)
Regulating the output current and reducing the harmonic distortion are key control problems in the airport navigation dimming power supply (DPS). In this study, a new method which could dynamically adjust P and I gains is presented for the DPS based on the radial basis function (RBF) neural networks combined with the gradient descent method. To implement the proposed method, the key factors which influence the performance of DPS are revealed by analyzing the dynamic response of the control system. The controller design process is presented in detail along with a system stability analysis. The correctness of theoretical derivation is examined through extensive digital computer simulation analyses in MATLAB while the comparative analysis is carried out under different operation conditions through experiments in a 30kW experimental prototype. The results indicate that the DPS adopting the method proposed in this paper could obtain better dynamic response and less harmonic content in various complex working conditions.